System of Rice Intensification - Chacón, Kattia (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Identifies the achievements made by farmers in reducing water consumption in rice cultivation, using innovative practices to face climate change and water scarcity, based on this interest, you collect examples of plaicacón in different countries according to their unique conditions with the methodology of the Intensive Rice Cultivation System (SICA).